Noninvasive prenatal diagnosis - Wei-Lun Cheng; Ching-Hua Hsiao; Hua-Wei Tseng; Tai-Ping Lee (Taiwanese Journal of Obstetrics & Gynecology, 2015)
Prenatal examination plays an important role in present medical diagnosis. It provides information on fetal health status as well as the diagnosis of fetal treatment feasibility. The diagnosis can provide peace of mind for the perspective mother. Timely pregnancy termination diagnosis can also be determined if required. Amniocentesis and chorionic villus sampling are two widely used invasive prenatal diagnostic procedures. To obtain complete fetal genetic information and avoid endangering the fetus, noninvasive prenatal diagnosis has become the vital goal of prenatal diagnosis. However, the development of a high-efficiency separation technology is required to obtain the scarce fetal cells from maternal circulation. In recent years, the rapid development of microfluidic systems has provided an effective method for fetal cell separation. Advantages such as rapid analysis of small samples, low cost, and various designs, greatly enhance the efficiency and convenience of using microfluidic systems for cell separation. In addition, microfluidic disks can be fully automated for high throughput of rare cell selection from blood samples. Therefore, the development of microfluidic applications in noninvasive prenatal diagnosis is unlimited.